2006
DOI: 10.1002/anie.200600414
|View full text |Cite
|
Sign up to set email alerts
|

A η4‐Dithio‐para‐benzoquinone Metal Complex

Abstract: Overcoming a long‐standing challenge: A rational synthetic procedure allows the isolation of the first stable η4‐dithio‐para‐benzoquinone complex (2; Cp*=C5Me5). The X‐ray molecular structure of 2 confirms the coordination of the elusive intermediate 1 in an η4 manner. Computational analyses of 2 support the role of the {Cp*Ir} fragment in stabilizing this reactive intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
0
26
1
2
Order By: Relevance
“…37 Computational analyses using DFT confirmed a net transfer of about 0.8 units of electron density to the p*-ligand lowest unoccupied molecular orbital. This additional electron density is largely localized around the thiocarbonyl bonds, resulting in a reduction in the C=S bond order as well as an anticipated decrease in the C=C bond order.…”
Section: Methodsmentioning
confidence: 95%
“…37 Computational analyses using DFT confirmed a net transfer of about 0.8 units of electron density to the p*-ligand lowest unoccupied molecular orbital. This additional electron density is largely localized around the thiocarbonyl bonds, resulting in a reduction in the C=S bond order as well as an anticipated decrease in the C=C bond order.…”
Section: Methodsmentioning
confidence: 95%
“…[59] Pursuing our research in this area, that is, stabilization of reactive intermediates, [60,61] we discovered that {Cp*Ir} can also stabilize the elusive o-and p-dithiobenzoquinone intermediates. [25] Our synthetic approach is completely different from that reported for the quinone methide. It involves the synthesis of halogenated 1, (9), which are the key molecules for 2 d and 2 e. Subsequent substitution of the chlorides by HS À provided the target compounds 2 d and 2 e in high yields (Scheme 8).…”
Section: Synthesis Of O-and P-dithiobenzoquinone As Metal Complexesmentioning
confidence: 97%
“…In only a few examples was a metalated bridging ligand used. [19][20][21] In contrast, we have recently found that our rhodium and iridium p-benzoquinone complexes [Cp*M(p-benzoquinone)] (M = Rh, L Rh ; M = Ir, L Ir ) are stable, easy to prepare, and adequate organometallic bridging ligands [22][23][24][25] to construct a novel family of supramolecular assemblies (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…[59] Im Zuge unserer Forschungen über die Stabilisierung reaktiver Intermediate [60,61] stellten wir fest, dass {Cp*Ir} auch die kurzlebigen o-und p-Dithiobenzochinon-Intermediate stabilisieren kann. [25] Unsere Synthesemethode umfasst die …”
Section: Neutrale O-und P-dithiobenzochinon-iridiumlinkerunclassified
“…Rh ; Ir, L Ir ) stabil sind, einfach hergestellt werden können und geeignete metallorganische Linker [22][23][24][25] zum Aufbau supramolekularer Strukturen ergeben (Abbildung 1).…”
Section: Introductionunclassified